Identification of a nitrogenase FeMo cofactor precursor on NifEN complex - Hu, Yilin (National Academy of Sciences, 2005)
The biosynthesis of the FeMo cofactor (FeMoco) of Azotobacter vinelandii nitrogenase presumably starts with the production of its Fe/S core by NifB (the nifB gene product). This core is subsequently processed on the α(2)β(2) tetrameric NifEN complex (formed by the nifE and nifN gene products). In this article, we identify a NifEN-bound FeMoco precursor form that can be converted to fully assembled FeMoco in a so-called FeMoco-maturation assay containing only purified components. We also establish that only molybdate, homocitrate, MgATP, and Fe protein are essential for FeMoco maturation. The FeMoco-maturation assay described here will further address the remaining questions related to the assembly mechanism of the ever-intriguing FeMoco.